A proposal by the Peruvian College of Physicians for Reforming Mental Health Care in Peru - Bojórquez Giraldo, Enrique (2012)
Since neuropsychiatric disorders are now the first component of disease burden in Peru, translating this into high prevalence rates for these conditions; and considering that - paradoxically - the Government has not assumed its responsibility, there is a need for proposing a reform of mental health management considering these fundamental aspects: 1) The Ministry of Health must assume its responsibility prioritizing mental health as a public health policy, creating a General Direction for Mental Health; 2) Psychiatric care must be restructured, joining forces with primary health care within the local health systems so that alternative community-centered models may be promoted within their social scope; 3) Personal dignity and human rights of every subject must be preserved; 4) Modernization of the current psychiatric institutions, changing their current hegemonic role to a superspecialization role, including advisory, teaching, and research. All of these aspects must be carried out within a, equity, universality, solidarity, accessibility, participation, quality, and efficiency framework .